Keynote: Additive Technologies for Medicine and Health - From sinter simulation of filigree dental parts to microphysiological systems for testing of radiopharmaceuticals (Transactions on Additive Manufacturing Meets Medicine, 2024)
Metal additive manufacturing for medicine has so far focused on laser-based processes (LPBF especially). These are characterized by a high technical maturity, but do not meet all the requirements in terms of materials, geometries and productivity. The industry is therefore increasingly focusing on sinter-based AM. These offer advantages such as processing materials that are difficult to weld, high productivity or high surface quality. As an example, clasp prostheses are a health insurance benefit and therefore give around half a million patients in Germany access to dentures every year. Their conventional production using model casting processes also requires an innovative alternative from an ecological point of view, as it is currently energy, time and labour-intensive and produces many by-products, some of which are harmful to health. Near-net-shape production of clasp prostheses using AM can reduce the consumption of resources, as well as the amount of hazardous waste produced. The conventional method is currently not economically viable for dental technicians due to the cost structure of production and the fees that health insurance companies pay for this service. Further examples covering a wide range of AM technologies will be presented and discussed economically and technically in this paper. An overview of expected developments for the next years will be also given.
Keywords: Dental Parts